Desmoplastic fibroblastoma (collagenous fibroma) in the oral cavity - Thomas Varghese; Karthigakannan Subramanian Pillai; Sreenivasan Bhargavan Sarojini; Ektah Khosla (Wolters Kluwer Medknow Publications, 2014)
Desmoplastic fibroblastoma (DF) also known as collagenous fibroma (CF) is a rare benign soft tissue tumor that occurs in varied locations in the body. Very few cases of DF have been reported in the oral cavity. We report a case of DF in an 8-year-old boy presented as a slow-growing mass in the buccal mucosa since 6 months. Histopathology, special staining and immunohistochemistry studies suggested a diagnosis of CF. As per our knowledge of the current literature this is the seventh case reported in the oral cavity and the first report in a child.